A genre-based investigation of the introduction sections of academic oral presentations / Kuldip Kaur Maktiar Singh … [et al.] - Maktiar Singh, Kuldip Kaur; Mohamad Ali, Afida; Chan, Mei Yuit; Tan, Helen (Universiti Teknologi MARA Cawangan Selangor, 2019)
The academic oral presentation (henceforth AOP) is an important genre for tertiary students across various courses and disciplines in the university. Despite the importance of AOPs for undergraduate students, relatively little is known about this genre. Using Swales’ (1990, 2004) notion of move analysis, this paper compares the rhetorical structure of the introduction sections of academic oral presentations from two different fields, namely English language and Administrative Sciences. The findings show some similarities in the AOPs whereby the introduction section contained three moves, and their related steps were similar to previous studies on the rhetorical structure of oral presentations but with few variations. The linguistic features used were also found to be similar in both corpora revealing that students were able to transfer their rhetorical knowledge and linguistic features from one context to another. This study reveals that variation in AOPs is possible in different courses and disciplines. Thus, having genre awareness can help students adapt their genre knowledge to the context.